2021
DOI: 10.1002/anie.202014941
|View full text |Cite
|
Sign up to set email alerts
|

Novel Series of Mononuclear Aluminum Complexes for High‐Performance Solution‐Processed Organic Light‐Emitting Devices

Abstract: Light metal complexes, such as lithium (Li), sodium (Na), magnesium (Mg), and aluminum (Al) complexes, are attractive candidates for the fabrication of thermally activated delayed fluorescent (TADF) materials. Nevertheless, mononuclear Al complexes with delayed fluorescence have not been developed so far. In this study, we successfully developed a novel series of highly luminescent Al complexes with two phenylacridine‐modified asymmetric acetylacetonate‐type ligands. These complexes exhibit high photoluminesce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Recently, Kido and coagent depicted an unusual series of highly luminescent TADF mononuclear Al complexes through coordinating with phenylacridine-modified asymmetric acetylacetonate-type ligands. [39] The design strategy is based on two expectations. For the one hand, mononuclear metal complex may cause higher PLQY and flexibility.…”
Section: Other Non-precious Metal Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Kido and coagent depicted an unusual series of highly luminescent TADF mononuclear Al complexes through coordinating with phenylacridine-modified asymmetric acetylacetonate-type ligands. [39] The design strategy is based on two expectations. For the one hand, mononuclear metal complex may cause higher PLQY and flexibility.…”
Section: Other Non-precious Metal Complexesmentioning
confidence: 99%
“…While the development of Al complexes is limited by the low EQE. Recently, Kido and coagent depicted an unusual series of highly luminescent TADF mononuclear Al complexes through coordinating with phenylacridine‐modified asymmetric acetylacetonate‐type ligands [39] . The design strategy is based on two expectations.…”
Section: Non‐traditional Phosphorescent Complexesmentioning
confidence: 99%
“…These complexes exhibit a high PLQY in the solid state. 264 Solution treatment of OLEDs using these Al(III) complexes showed remarkable properties at 100 cd m À2 with an EQE (external quantum efficiency) of 17.5%. These are the best properties recorded so far for light metal-based TADF OLEDs.…”
Section: Organic-inorganic Hybrid System: Tadfmentioning
confidence: 97%
“…In addition, as mentioned above, a vacuum-deposited OLED always provides a better device performance than that made from solution processing. However, In 2021, Nakao et al reported two mononuclear Al(III) complexes that coordinate with phenylacridine-modified asymmetric acetylacetonate-type ligands [213]. The chemical structure and OLED performance of these complexes are described in figure 31(b).…”
Section: Metal-complex Tadf Emittersmentioning
confidence: 99%